let i, j be Nat; :: thesis: for G being Go-board st 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G holds
(LSeg ((G * (i,j)),(G * ((i + 1),j)))) /\ (LSeg ((G * ((i + 1),j)),(G * ((i + 1),(j + 1))))) = {(G * ((i + 1),j))}

let G be Go-board; :: thesis: ( 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G implies (LSeg ((G * (i,j)),(G * ((i + 1),j)))) /\ (LSeg ((G * ((i + 1),j)),(G * ((i + 1),(j + 1))))) = {(G * ((i + 1),j))} )
assume that
A1: 1 <= i and
A2: i + 1 <= len G and
A3: 1 <= j and
A4: j + 1 <= width G ; :: thesis: (LSeg ((G * (i,j)),(G * ((i + 1),j)))) /\ (LSeg ((G * ((i + 1),j)),(G * ((i + 1),(j + 1))))) = {(G * ((i + 1),j))}
now :: thesis: for x being object holds
( ( x in (LSeg ((G * (i,j)),(G * ((i + 1),j)))) /\ (LSeg ((G * ((i + 1),j)),(G * ((i + 1),(j + 1))))) implies x = G * ((i + 1),j) ) & ( x = G * ((i + 1),j) implies x in (LSeg ((G * (i,j)),(G * ((i + 1),j)))) /\ (LSeg ((G * ((i + 1),j)),(G * ((i + 1),(j + 1))))) ) )
let x be object ; :: thesis: ( ( x in (LSeg ((G * (i,j)),(G * ((i + 1),j)))) /\ (LSeg ((G * ((i + 1),j)),(G * ((i + 1),(j + 1))))) implies x = G * ((i + 1),j) ) & ( x = G * ((i + 1),j) implies x in (LSeg ((G * (i,j)),(G * ((i + 1),j)))) /\ (LSeg ((G * ((i + 1),j)),(G * ((i + 1),(j + 1))))) ) )
hereby :: thesis: ( x = G * ((i + 1),j) implies x in (LSeg ((G * (i,j)),(G * ((i + 1),j)))) /\ (LSeg ((G * ((i + 1),j)),(G * ((i + 1),(j + 1))))) )
assume A5: x in (LSeg ((G * (i,j)),(G * ((i + 1),j)))) /\ (LSeg ((G * ((i + 1),j)),(G * ((i + 1),(j + 1))))) ; :: thesis: x = G * ((i + 1),j)
then reconsider p = x as Point of () ;
A6: x in LSeg ((G * (i,j)),(G * ((i + 1),j))) by ;
A7: p in LSeg ((G * ((i + 1),j)),(G * ((i + 1),(j + 1)))) by ;
A8: ( 1 <= j + 1 & 1 <= i + 1 ) by NAT_1:11;
j < j + 1 by XREAL_1:29;
then A9: j <= width G by ;
A10: 1 <= i + 1 by NAT_1:11;
then (G * ((i + 1),j)) `1 = (G * ((i + 1),1)) `1 by
.= (G * ((i + 1),(j + 1))) `1 by ;
then A11: p `1 = (G * ((i + 1),j)) `1 by ;
i <= i + 1 by NAT_1:11;
then i <= len G by ;
then (G * (i,j)) `2 = (G * (1,j)) `2 by
.= (G * ((i + 1),j)) `2 by ;
then p `2 = (G * ((i + 1),j)) `2 by ;
hence x = G * ((i + 1),j) by ; :: thesis: verum
end;
assume x = G * ((i + 1),j) ; :: thesis: x in (LSeg ((G * (i,j)),(G * ((i + 1),j)))) /\ (LSeg ((G * ((i + 1),j)),(G * ((i + 1),(j + 1)))))
then ( x in LSeg ((G * (i,j)),(G * ((i + 1),j))) & x in LSeg ((G * ((i + 1),j)),(G * ((i + 1),(j + 1)))) ) by RLTOPSP1:68;
hence x in (LSeg ((G * (i,j)),(G * ((i + 1),j)))) /\ (LSeg ((G * ((i + 1),j)),(G * ((i + 1),(j + 1))))) by XBOOLE_0:def 4; :: thesis: verum
end;
hence (LSeg ((G * (i,j)),(G * ((i + 1),j)))) /\ (LSeg ((G * ((i + 1),j)),(G * ((i + 1),(j + 1))))) = {(G * ((i + 1),j))} by TARSKI:def 1; :: thesis: verum